Critical success factors and improvements in ISO 9000 maintenance / Roslina Ab Wahid and James Corner - Ab Wahid, Roslina; Corner, James (Institute of Business Excellent (IBE), 2011)
The purpose of the ISO 9000 standards is to facilitate the multinational exchange of products and services by providing a clear set of quality systems requirements. It is also to assist organizations of all sectors and sizes to implement and operate an effective quality management system (QMS). The generic nature of the standards allows interested companies to determine the specifics of how the standards apply to its organization. Registration or certification to the standards demonstrates to customers that the supplying organization has achieved a basic level of quality assurance by the formalization and documentation of its quality management system. However, there is a lacking in the literature on the post-certification period as most of the published work focuses on how to obtain certification and the impact of certification on ISO 9000-certified companies. Thus, studies do not generally address what happens after the companies have obtained their certification.